The Gist of Delay of Gratification: Understanding and Predicting Problem Behaviors. (10th August 2016) - Reyna, Valerie F.; Wilhelms, Evan A.
Abstract: Delay of gratification captures elements of temptation and self‐denial that characterize real‐life problems with money and other problem behaviors such as unhealthy risk taking. According to fuzzy‐trace theory, decision makers mentally represent social values such as delay of gratification in a coarse but meaningful form of memory called "gist." Applying this theory, we developed a gist measure of delay of gratification that does not involve quantitative trade‐offs (as delay discounting does) and hypothesize that this construct explains unique variance beyond sensation seeking and inhibition in accounting for problem behaviors. Across four studies, we examine this Delay‐of‐gratification Gist Scale by using principal components analyses and evaluating convergent and divergent validity with other potentially related scales such as Future Orientation, Propensity to Plan, Time Perspectives Inventory, Spendthrift‐Tightwad, Sensation Seeking, Cognitive Reflection, Barratt Impulsiveness, and the Monetary Choice Questionnaire (delay discounting). The new 12‐item measure captured a single dimension of delay of gratification, correlated as predicted with other scales, but accounted for unique variance in predicting such outcomes as overdrawing bank accounts, substance abuse, and overall subjective well‐being. Results support a theoretical distinction between reward‐related approach motivation, including sensation seeking, and inhibitory faculties, including cognitive reflection. However, individuals' agreement with the qualitative gist of delay of gratification, as expressed in many cultural traditions, could not be reduced to such dualist distinctions nor to quantitative conceptions of delay discounting, shedding light on mechanisms of self‐control and risk taking. Copyright © 2016 John Wiley & Sons, Ltd.